Genetic Variation, Clonal Selection and Balance Polymorphism in Natural Populations of Cyclic Parthenogenetic Rose Aphids (Macrosiphum rosae) - Joseph, Sheila (My University, 1981)
This study was undertaken to assess the role of natural selection in the maintenance of genetic variation in natural population of Rose Aphids (Macrosiphum rosae). The selection of rose aphids as organism of choice was based on three features common to all aphids. (1) Their habitat with respect to food (host-plants) is well defined, (2) Their migration potential is large enough that geographical differentiation of allele frequencies are not expected, and (3) Aphids are cyclic parthenogenetic which allows to investigate the role of seasonal change and variation in breeding system on the amount and pattern of genetic variation. A total of nine geographic (Detroit, London, Hamilton, Niagara Falls, Rochester, Syracuse and New York City) and eleven local populations (Hamilton, Ontario) were studied for one morphologoical and fourteen allozyme loci. On an average about thirty percent of loci were polymorphic and an individual was heterozygous for about 4.3% of its genome. All geographical populations expect Detroit and New York had roughly similar allele frequencies. The latter two populations differed somewhat from the rest and these changes are thought to be due to temporal rather than geographical factors. The local variations at eleven sites in Hamilton was remarkably similar to the macrogeographic pattern of variation. Six local populations in Hamilton were studied for temporal variation using four polymorphic loci. All loci showed large genotypic fluctuations over time but the variation at only one locus (Esterase-4) was cyolic in nature. However, the occurrence of intermediate allele frequencies and the temporal changes at all four polymorphic loci strongly suggest that these polymorphism are maintained by balancing selection. The balancing selection in this case is thought to be of the type where genotypes have different fitness during the sexual and asexual generations. Since during the asexual generations, selection acts in the whole genome (clonal selection) any directional change is allele frequencies, whether due to natural selection or hitch hike, must be balance presumably by changes during the sexual generation. In this view the cyclic parthenogenetic breeding system appears to be directly involved in shaping the structure of genetic variation in rose aphids.
Keywords: Biology; Biology